Characterisation of DODAC lamellar gel phase in the presence of additives - Steven (2019)
Dioctadecyldimethylammonium chloride (DODAC) is a type of cationic surfactant that is frequently used in household products such as fabric softener and hair conditioner. This is due to its lamellar phases that has excellent conditioning benefits, with the liquid crystalline phase (Lα) existing above gel melting temperature (Tm) of around 45 oC, which has good swelling potential for molecule delivery. However, the typical usage at room temperature proves this Tm to limit its applicability, and it causes the need to use additives that maintain the structure and tune its Tm for optimum usage, which in the past were mostly studied on zwitterionic and nonionic surfactants. In this study, the effects of two types of additives will be investigated on DODAC; hydrotropes which includes succinic acid and 1,3-butanediol, and co-surfactants which comprises of fatty alcohols with varying n-alkanol chain length from 4 to 12 carbons. These additives will be tested for their affects by preparing DODAC-additive-water ternary system with two approaches; (1) – addition of additives, (2) – addition of water. These samples would then be characterised using differential scanning calorimetry (DSC), polarized optical microscopy (POM), and small/wide angle X-ray scattering (SWAXS). The results suggest that succinic acid acted as a polar additive which did not have any effect towards the surfactant conformation, while 1,3-butanediol is generally polar, but has shown a slight contribution to lower the surfactant Tm. On the other hand, fatty alcohol mixtures have distinct properties depending on the additive alkyl chain length. For short-chain lengths (C4-8), it generally exhibited hydrotropic properties, significantly lowering the Tm, with C6 and C8 also displayed phase separation. For long chain lengths (C10-12), it increases the surfactant gel stability by showing an increase of Tm with the addition of fatty alcohols above 1:1 surfactant-to-additive ratio. This study proves that further studies on DODAC phase behaviour due to additives that constitutes personal care formulations are important. Furthermore, recommendations were also proposed to provide a better insight to study the molecular interactions.